Política Industrial de Desenvolvimento Regional: o caso de Sergipe no período de 1995 a 2002 - Ribeiro, Ulisses Pereira (2005)
This study is about the industrial politics and regional development and its aim is analyse the efficacy of the Sergipano Industrial Development Program - PSDI as a strategy of lasting regional and local development. Bibliographic, document and camp research were done in order to carry out this study. The camp research was done from an application of a questionnaire the 50% of the firms that are supported by the PSDI and are located in cities at Sergipe State that represent the biggest area of action of the Program, taking into consideration the resources concentration, the number of supported enterprises, jobs, according to information given by Sergipe Industrial Development and Mineral resources - CODISE. Those cities are Aracaju, Estância and Nossa Senhora do Socorro. In spite of the space concentration, the PSDI reached an area bigger than one resaulting from the politics implemented at the 70s and 80s, even though the economic rising rithm it is much more modest than at the period before. Concerned to the level of the supported enterprises to the sergipano territory, it was observed that just one of the firms got a high rate. This firm produces concentrated fruit juice and has a strong relationship with the South Region of Sergipe with the economy and society - fruit producer area, mainly orange. That firm has contributed to the regional development when wakes stronger the production network of the Region focusing the product destination the abroad market. However, the average level of adherence at the studied group, it is 51% of the maximum mark that could be done. It shows the serious fragility of the industrialization promoted by the PSDI. The agreement among businessmen and the State government about the productive structure implantation or enlargement projects, sometimes are not Kept, mainly when it refers to the number of the jobs and the enviroment preservation. Another detected problem was the type of plot made. For the majority of the supported activities it is done just at a vertical way without link with the local actors directed to make the productive sectors of the territory stronger. So, the implemented strategy for the Sergipano government at the studied period shows serious fragility. Those problems make infeasible a lasting process of development, even thought, at first, their results are positive.